Using big data to assess the economic potential of organizations - M. N. Smagina; N. M. Sugrobova; A. А. Novikova (Путеводитель предпринимателя, 2020)
The article of the economic potential depends on the availability of a stable state in which the company is able to make timely payments and Finance its own activities. The success of an enterprise is unthinkable without the availability of timely and reliable information about the state of the market, in which a large number of competing companies are forced to continuously lower their margins. Those who are able to objectively evaluate the huge flows of information about the state of the market and respond accordingly to them come out as the winner in this «arena», for this purpose, work with «Big data» is performed.